Purchasing Power Parity and New Trade Theory - Ricci, Luca (IMF Working Papers; Working Paper ;, 2002)
This paper theoretically derives and empirically tests the implications of a new trade theory framework for the systematic movements in the real exchange rate. It focuses on the effect of imperfect substitutability of tradables and on the importance of competitiveness, for which we construct an original proxy. Using a panel dynamic OLS estimation of nine bilateral US dollar real exchange rates, we derive long-run coefficients for relative productivity and competitiveness in the tradable and non-tradable sectors, controlling for standard macroeconomic variables. The implications of imperfect substitutability of tradables fit the data better than the standard neoclassical assumption of price equalization. Our new measure of competitiveness is statistically significant in explaining deviations from PPP.